2011
DOI: 10.1038/hr.2010.274
|View full text |Cite
|
Sign up to set email alerts
|

Association of (pro)renin receptor gene polymorphisms with lacunar infarction and left ventricular hypertrophy in Japanese women: the Ohasama study

Abstract: Recent studies have revealed that (pro)renin receptor ((P)RR), a newly identified member of the renin-angiotensin system, is associated with organ damage that occurs with cardiovascular disease. We investigated the association of genetic polymorphisms in the (P)RR gene with lacunar infarction, white matter hyperintensity and left ventricular hypertrophy (LVH) in a Japanese general population recruited from the Ohasama study, a Japanese cohort study. A total of 779 subjects (men¼250 and women¼529) were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Firstly, the 5+169C>T polymorphism was significantly associated to blood pressure in Japanese men [46] and more recently also in Caucasian men [47]. Secondly, the +1513A>G polymorphism was significantly associated with the risk of lacunar infarction and left ventricular hypertrophy in Japanese women [48]. Finally, two additional polymorphisms were significantly associated with hypertension in additional populations with vascular diseases [49].…”
Section: Humanmentioning
confidence: 92%
“…Firstly, the 5+169C>T polymorphism was significantly associated to blood pressure in Japanese men [46] and more recently also in Caucasian men [47]. Secondly, the +1513A>G polymorphism was significantly associated with the risk of lacunar infarction and left ventricular hypertrophy in Japanese women [48]. Finally, two additional polymorphisms were significantly associated with hypertension in additional populations with vascular diseases [49].…”
Section: Humanmentioning
confidence: 92%
“…Transgenic overexpression of the (P)RR in rats causes elevated blood pressure (29). Of note, polymorphism in the (P)RR gene is associated with a high blood pressure in men (IVS5+169C>T) and left-ventricular hypertrophy in women (+1513A>G) (30,31). High (P)RR mRNA and protein levels observed in the fetal heart suggest a role for (P)RR in heart development.…”
Section: Discussionmentioning
confidence: 99%
“…Also, another major finding ) stated that (P)RR play essential role in neuronal cell differentiation. Other than the embryonic development, (P)RR gene polymorphism has been found to be associated with high blood pressure in Caucasian and Japanese male subjects (Hirose et al, 2011;Ott et al, 2011). Elevated blood pressure and increased heart rate in transgenic rats over expressing (P)RR in smooth muscles have been reported in their models .…”
Section: Functions Of (P)rr Other Than Its Involvement In Renin-angiomentioning
confidence: 99%
“…These data demonstrated the possible involvement of (P)RR in the pathogenesis of heart failure and kidney tissue damage. Association of (P)RR gene polymorphism with high blood pressure and left ventricular hypertrophy substantiate the important role of (P)RR in the pathogenesis of hypertension in humans (Hirose et al, 2011;Ott et al, 2011) In vitro and animal studies have shown that increased receptor expression could be linked to high blood pressure and to cardiac and glomerular fibrosis by activating mitogen-activated protein kinases and by upregulating gene expression of profibrotic molecules. Also, animal studies with angiotensin-II type 1a receptor deficiency showed that the (P)RR is involved in the development and progression of diabetic nephropathy through angiotensin-II independent pathway via activation of intracellular pathways (Ichihara et al, 2006c).…”
Section: Pathophysiology Of Prorenin and (Pro)renin Receptormentioning
confidence: 99%